THE HISTORY OF STUDYING WOMEN’S JEWELRY ATTIRE OF SMOLENSK-POLOTSK LONG BARROWS CULTURE: RESULTS AND THE CURRENT STATE (City: History, Culture, Society, 2021)
The article is devoted to the history of studying, as well as to the analysis of how deeply women’s metal attire (suit) of Smolensk-Polotsk long barrows culture is studied, which is usually identified with the Krivichs from annalistic chronicles. The author analyzed a number of scientific publications, on the basis of which it was concluded that a focused study of this issue had begun in the 1960s. In the studies of women’s jewellery attire of the Krivichs three periods can be distinguished. The initial period (1960s – early 1990s) is characterized by a gradual departure from the perception of women’s attire of “the culture of long barrows” only as a source of research. Attire became the subject of research.The second period (1990s – 2017) is characterized by studying of women’s attire in terms of the Culture of Smolensk-Polotsk Long Barrows (SPLBK) on purpose. At that time, fairly detailed typologies of particular elements of the SPLBK women’s attire appeared. Since 2017 the third period has begun (2017 – present). It is determined based on discovery of moundless burials of the KSPDK in which new “atypical” women’s jewellery is found. It makes researchers rethink the tradition of a funeral rite and specific elements of the Krivichi women’s attire E.A. Schmidt, V.V. Sedov, V.V. Enukov, V.S. Nefyodov are among the main researchers. As a result of multiple years research, things that act as “cultural markers” were identified. Typologies and a chronology of individual elements of women’s metal attire were suggested: temple rings, head ornaments, holders. It has been established that in the study of women’s jewellery attire SPLBK the “micro-regional approach” prevails: typologies of inventory are predominantly based on materials from Smolensk part of the cultural area. Thus, there is a ‘gap’ between Russian and Belarusian researchers in how deeply women’s metal attire is studied.In Belarus, the study of its local characteristics and chronology has just begun.
Keywords: Smolensk-Polotsk long barrows culture; Belarusian Dvina region; women’s jewelry attire; E.A. Schmidt; V.V. Sedov; V.V. Enukov; V.S. Nefyodov; Krivichi